A report to the Committee on the Nobel Prize in Economic Science, 1985: the contributions of James M. Buchanan to economics and political economy - Thomas E. Borcherding (Claremont McKenna College, Department of Economics, 2002)
Buchanan's contributions through 1984 are surveyed in six areas: (A) debt, fiscal illusion, and Keynesian criticisms, (B) London School of Economics cost approach, (C) methodological individualism and the economics of politics, (D) welfare price theory, (E) rent-seeking and polity failure, and (F) political economy and constitutions. A comprehensive bibliography of ten books, four monographs, forty-three refereed articles, thirty essays in books, ten short papers, thirty-three papers in collected works, and a translation is offered.
Keywords: 330; Wirtschaftswissenschaftler; Nobelpreis